Marine-mollusc fossils (Mollusca: Bivalvia and Gastropoda) and their paleoenvironmental interpretation from the Situs Manusia Purba Sangiran area - Yudha, Donan Satria (2016)
Research on mollusc fossils on the Sangiran area is not widely known. Sangiran area is known as one of the world prehistoric sites, because the area has uncovered many fossil organisms. Sangiran stratigraphic chart extend from the oldest geological time to recent one, i.e.: Late Pliocene to Holocene. The stratigraphic chart is divided into 4 formations, i.e: Kalibeng, Pucangan, Kabuh and Notopuro. Each formation is characterized by different geological sediments and distinctive fossil organisms. The Laboratory of Bioanthropology and Paleoanthropology, Faculty of Medicine, UGM has been frequently conducting excavation in the Sangiran area. Fossil of marine molluscs that had been found so far are not yet identified. The aims of this research are: to identify fossil collection of marine-molluscs in order to study its diversity during the Pleistocene, and to interpret the paleo-environment of where those fossils were found. The results obtained: from 35 sampels of bivalve there are 6 orders with 12 families and 3 identified genera. From twenty nine samples of gastropod there are 4 orders with 14 families and 13 identified genera. All identified genera of bivalves and gastropods are fauna which habitat in the shallow sea of intertidal zone. These marine molluscs habitat is match with the geological studies of Sangiran area in which during the Lower Pleistocene, some part of Sangiran area were shallow sea and estuaries.